Propranolol therapy in 55 infants with infantile hemangioma: dosage, duration, adverse effects, and outcome - Schupp, Christine; Kleber, Johann-Baptist; Günther, Patrick; Holland-Cunz, Stefan (Pediatric dermatology, 2011)
Abstract: Propranolol has recently been reported to be a highly effective treatment for infantile hemangioma (IH) and is emerging as a first-line therapy. This study reports the observations after completed propranolol therapy in 55 patients. Propranolol was administered in a dosage of 2 mg/kg per day with initial monitoring of vital signs. Therapy duration was planned for 4 to 6 months; if there was significant relapse, the period of treatment was extended. The mean age of 55 patients at the beginning of the treatment was 6 months (52.7% <4 mos, 30.9% 4-9 mos, 16.3% >9 mos). Thirteen patients (21.7%) showed a reaction possibly due to the medication, but we did not observe any life-threatening adverse effects. The therapy was interrupted due to temporary aggravation of preexisting bronchial asthma in one child. The initially administered dosage was adjusted to the increase of weight in 21 patients (38.2%), but most did not require a dosage adjustment despite somatic growth. Mean duration of treatment was 6 months; younger patients needed longer treatment periods. Response to treatment was favorable; eight (14.5%) showed total regression and 46 (83.4%) partial regression, and one (1.8%) had no response. Propranolol is an efficacious therapy for severe IH. Risks and complications appear moderate. If indicated, therapy should be initiated early to minimize the extent of residual changes. Young patients show quick and extended benefit. Prospective controlled trails are necessary to observe the effects on a long-term basis.
Gesehen am 28.10.2022